2021
DOI: 10.3389/fpsyg.2021.641919
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between SNS Usage and Disordered Eating Behaviors: A Meta-Analysis

Abstract: Social Networking Sites (SNSs) are common tools with which modern people share their lives and establish social relationships. However, some studies have found SNSs to be associated with eating disorders, although other have identified no connection between the two. To explore the interaction between SNSs and eating disorder behaviors, this study aimed to comprehensively synthesize previous studies using meta-analysis methods. Based on selection criteria, there were 87 effect sizes from 22 studies. After analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 108 publications
(115 reference statements)
2
26
1
2
Order By: Relevance
“…Problematic Facebook use is on the rise [ 20 ]. It has a causal effect on eating disorder symptoms and attitudes [ 35 37 , 40 , 41 ]. Comorbid dependence on Facebook/internet increases emotional negativity (e.g., depression and state anxiety) in individuals prone to disordered eating [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problematic Facebook use is on the rise [ 20 ]. It has a causal effect on eating disorder symptoms and attitudes [ 35 37 , 40 , 41 ]. Comorbid dependence on Facebook/internet increases emotional negativity (e.g., depression and state anxiety) in individuals prone to disordered eating [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of dysfunctional eating are more likely to be internet dependent while internet addiction is a confirmed predictor of all subtypes of EDs among university students [ 33 , 34 ]. Indeed, meta-analytic data confirm causal claims associating SNSs/Facebook use and disordered eating [ 35 ]. Facebook implicates numerous factors that increase the risk for eating pathology such as media and peers [ 34 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 94%
“…Meta‐analyses and reviews link social media use to poorer body image and disordered eating (de Valle et al, 2021; Frost & Rickwood, 2017; Holland & Tiggemann, 2016; Mingoia et al, 2017; Ryding & Kuss, 2019; Saiphoo & Vahedi, 2019; Zhang et al, 2021). Across reviews, appearance‐related use (i.e., exposure to appearance‐ideal images; posting photos of oneself; viewing/liking/commenting on others' photos; and appearance‐related social media motivations) has stronger associations with negative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…(27). A recent meta-analysis of 22 studies across various countries by Zhang et al found an adverse relationship between use of social networking sites and disordered eating behaviors (28). For example, individuals exposed to weight-related stigma in experimental settings have been shown to have increased ad libitum total energy intake (29)(30)(31), to be more likely to binge eat and less likely to adhere to weight loss treatments (32,33), and to be less likely to engage in physical activity (31,(34)(35)(36)(37)(38)(39).…”
Section: Weight Stigma and Healthmentioning
confidence: 99%